Sex differences in patients with COVID-19 after bariatric surgery: a multicenter cross-sectional study - Wang, Senlin; Jang, Qiubai; Wang, Han; Yang, Yunning; Ruan, Min; Yu, Juan; Li, Xiuying; Luo, Dan (Frontiers in Public Health, 2024)
Objectives This multicenter, cross-sectional study aimed to investigate whether sex differences persist among patients who have undergone bariatric surgery and tested positive for the coronavirus disease (COVID-19). Methods We conducted a multicenter cross-sectional study via an online electronic questionnaire to collect data. Categorical data were presented as absolute and relative frequencies. Data for continuous variables were expressed as mean and standard deviation (SD) or median [interquartile range (IQR)]. We employed ordered logistic regression to assess whether females had higher odds of an increased self-reported duration of the most severe symptom compared to males. Using a modified Poisson regression model with robust standard errors to assess the differences in clinical characteristics among COVID-19 cases. Results Statistical analysis revealed significant differences in the prevalence rates of various comorbidities. Among participants who reported their temperature during COVID-19 infection, more than half engaged in vitamin supplementation and regular exercise, while 4.2% remained asymptomatic. The probability of females experiencing a longer duration of severe symptoms increased compared to males [adjusted Odds Ratio (aOR) = 1.92, 95% confidence interval (CI) 1.73–2.12]. In the multivariate mixed-effects Poisson regression analysis, compared to males, females exhibited a lower prevalence rate of asymptomatic infection [adjusted prevalence ratio (aPR 0.40, 95% CI 0.28–0.58), lower prevalence of infection without therapeutic medication use (aPR 0.76, 95% CI 0.70–0.82), and lower prevalence of multiple infections (aPR 0.39, 95% CI 0.20–0.74)]. Conclusion This cross-sectional study indicates the persistence of sex differences among patients with COVID-19 who have undergone bariatric surgery. Further research is needed to explore the underlying factors contributing to this disparity.